Impact of dexamethasone on cardiac injury in critically ill COVID-19 patients. (3rd October 2022) - Van Almsick, V; Jirak, P; Dimitroulis, D; Mirna, M; Seelmaier, C; Shomanova, Z; Semo, D; Dankl, D; Mahringer, M; Lichtenauer, M; Hoppe, U; Reinecke, H; et al.
Abstract: Aims/Background: Severe COVID-19 pneumonia requiring intensive care treatment remains a clinical challenge to date. Dexamethasone was reported as a promising treatment option, leading to a reduction of mortality rates in severe COVID-19 disease as well as ventilator-dependent days. However, the effect of dexamethasone treatment on cardiovascular outcomes including cardiac injury monitored by cardiac enzymes remains largely elusive. Methods: For this study, we retrospectively screened 224 consecutive COVID-19 patients between 4/2020 and 1/2021 in three Europeen Hospitals. To avoid bias effects of further applied COVID-19 specific medications including tacilizumab, remdesevir and sarilumab, 46 patients treated with at least one of these substances were excluded from further analyses. In total 178 critically ill COVID-19 patients requiring intensive care treatment and mechanical ventilation were recruited. 113 patients (63.5%) were treated with dexamethasone for a median duration of 10 days (IQR 9–10). 65 patients (36.5%) constituted the non-dexamethasone group. The assessment of cardiac injury was based on cardiac enzymes. Results: Baseline charactaristics shown in Tab. 1. While peak inflammatory markers seemed to be reduced by dexamethasone treatment (CRP and a trend towards decrease of interleukin 6 levels (CRP maximum level: median: 20 ng/mL (IQR 12–28) vs. 22 ng/mL (IQR 14–37), p=0.043; IL-6 maximum level: median: 192 pg/mL (IQR 78–533) vs. 708 pg/mL (550–885), p=0.085), in the dexamethasone Group also shown a significant reduction in peak troponine levels as shown in Figure 1. CK and CK-MB do not differ significantly by Dexamethasone application. Of note, no significant changes in baseline characteristics were observed between the dexamethasone and non-dexamethasone group (Table 1). Conclusion: In severe COVID-19, antiinflammatory effects of dexamethasone treatment could be associated with a significant reduction in myocardial injury. Further studies should further evaluate whether Dexamethasone effects directly myocardial involvement in COVID 19. Funding Acknowledgement: Type of funding sources: None.